2009
DOI: 10.2174/1874372200903010073
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Early Diet on Canine Atopic Dermatitis (CAD) in Three High-Risk Breeds

Abstract: Abstract:The effect of diet on the occurrence of canine atopic dermatitis (CAD) in the high-risk breeds boxer, English bull terrier and West Highland white terrier was investigated as part of an extensive case-control study. In that study, a sparing association was seen for feeding the bitch a diet containing non-commercial ingredients during lactation and the subsequent development of CAD in the offspring. The purpose of this study was to further explore the role of diet of the bitch during lactation as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 13 publications
2
3
2
Order By: Relevance
“…During the early and late postnatal periods, there were significant negative associations between the NPMD and incidence of IBD for the same dogs later in life. These findings are in accordance with several studies, which stated that a raw meat-based diet stimulated the growth of a balanced gut microbiome in healthy dogs which improved their gut function in comparison to dogs fed an extruded dry food (28,30,36,67). Our observations are in accordance with the hygiene hypothesis, which states that the more microbial exposures in the early life, the more developed immune system in adulthood (22,23).…”
Section: Modifiable Exposures and How They Related To Owner Reported Ibdsupporting
confidence: 93%
“…During the early and late postnatal periods, there were significant negative associations between the NPMD and incidence of IBD for the same dogs later in life. These findings are in accordance with several studies, which stated that a raw meat-based diet stimulated the growth of a balanced gut microbiome in healthy dogs which improved their gut function in comparison to dogs fed an extruded dry food (28,30,36,67). Our observations are in accordance with the hygiene hypothesis, which states that the more microbial exposures in the early life, the more developed immune system in adulthood (22,23).…”
Section: Modifiable Exposures and How They Related To Owner Reported Ibdsupporting
confidence: 93%
“…These findings support our previous observation that the consumption of a nonprocessed meat‐based diet during puppyhood may protect against AD in dogs later in life 11 . Interestingly, in an epidemiological study on 106 dogs, Sallander et al 26 found that feeding puppies noncommercial homemade diets that included minced beef from 2 to 6 months of age was significantly associated with a higher risk of CAD incidence, but this was true only if the dam was not fed homemade diets including meat, egg and milk products during lactation. When the dam was fed what the authors called noncommercial animal products during lactation, there was no difference in AD risk for the offspring, regardless if puppies were fed meat or not.…”
Section: Discussionsupporting
confidence: 90%
“…When the dam was fed what the authors called noncommercial animal products during lactation, there was no difference in AD risk for the offspring, regardless if puppies were fed meat or not. 26 The previous study highlights the importance of the diet of the dam, especially among high‐risk breeds for CAD.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the NPMD is highly palatable, the proteins and fats are highly digestible, it reduces blood triglycerides, maintains fecal quality and serum chemistry, and modifies the fecal microbiota community in adult dogs [80]. Moreover, eating a NPMD provides a variety of microbes when compared to eating UPCD, as the latter one is heat processed, which consequently kills the bacteria, making it sterile [40]. There is an indication that the transmission of microbiota from the intrauterine environment to the fetus may occur during pregnancy which seems to have a better impact on offspring future health [81].…”
Section: Prenatal Modifiable Variablesmentioning
confidence: 99%
“…As in humans, recent studies have shown that maternal diet during lactation has an effect on the development of allergies in canines [40,41]. The impact of the diet on human and canine health is not only tied to their macro-or micronutrient content but also to the processing; whether the food items are consumed as raw / non-processed or as ultra-processed diets, or mixes of them, as described in the NOVA guidelines [42][43][44][45].…”
Section: Introductionmentioning
confidence: 99%